1995
DOI: 10.1074/jbc.270.46.27728
|View full text |Cite
|
Sign up to set email alerts
|

Structural Organization and Chromosomal Assignment of the Human obese Gene

Abstract: The obese (ob) gene has been identified through a positional cloning approach; the mutation of this gene causes marked hereditary obesity and diabetes mellitus in mice. We report here the isolation and characterization of the human ob gene. Southern blot analysis demonstrated a single copy of the ob gene in the human genome. The human ob gene spanned approximately 20 kilobases (kb) and contained three exons separated by two introns. The first intron, approximately 10.6 kb in size, occurred in the 5'-untranslat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
63
0
11

Year Published

1996
1996
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 151 publications
(74 citation statements)
references
References 29 publications
0
63
0
11
Order By: Relevance
“…The partial sequence of the gene identi®ed in this study (data not shown) was identical to sequences published after the termination of the present study (GeneBank accession number D63709 and D63710). 18 The coding region is contained in exons 2 and 3 which in this study have been analysed by PCR-SSCP and heteroduplex analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The partial sequence of the gene identi®ed in this study (data not shown) was identical to sequences published after the termination of the present study (GeneBank accession number D63709 and D63710). 18 The coding region is contained in exons 2 and 3 which in this study have been analysed by PCR-SSCP and heteroduplex analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Differentiated adipocytes can function in an endocrine manner to secrete several cytokines, called ''adipokines,'' which include TNF-a, IL-6, leptin, adiponectin, and others (Spiegelman and Flier 1996;Matsuzawa et al 1999). These genes are found to contain binding sites for TFAP2 in their promoter (Kroeger and Abraham 1996;Isse et al 1995;Takahashi et al 2000). Given such observations, we suggest that TFAP2B plays a key role in the pathogenesis of type 2 A d ip o c y t e B r a in H e a r t K id n e y L iv e r L u n g P a n c r e a s P la c e n t a S k e le t a l m u s c le T h y m u s F e t a l B r a in F e t a l k id n e y F e t a l lu n g A d ip o c y t e B r a in H e a r t K id n e y L iv e r L u n g P la c e n t a S k e le t a l m u s c le ND P a n c r e a s Fig.…”
Section: Discussionmentioning
confidence: 99%
“…First strand cDNA was synthesised from 0.5 mg of total RNA using random hexamers in the presence of ditiothreitol and RNAse inhibitors. Specific primers of leptin 28 (GenBank D63710), TNFa 29 (GenBank X02910) and human beta-actin 30 (GenBank M10277) were derived from the gene sequences published in GeneBank. PCR reactions were performed in a thermocycler (Progene Techne, Cambridge).…”
Section: Plasma Biochemical Analysismentioning
confidence: 99%